Water distribution and water use assessment in rice cropping systems - S.M. Bockari-Gevao (Songklanakarin Journal of Science and Technology (SJST), 2006)
This study was carried out to analyze the ways of water distribution in a rice growing area during the pre-saturation and normal irrigation supply periods and to assess water use (WU). The analyses were conducted using field data collected at the Besut rice irrigation scheme located in the state of Terengganu, Malaysia. The scheme comprises two sub-schemes, which are further subdivided into compartments and blocks. Based on field water requirements during the pre-saturation and normal irrigation supply periods and available flows at the intake structures, canal simulation was performed using the CanalMan Model. Results have shown that pre-saturation should not be done continuously unless flow rates are 9.00 m3/sec and 3.00 m3/sec for the Besut and Angga Barrages, respectively. If the respective flow rates fall below these values, then pre-saturation should be done in two phases. However, when the flow rate is between 5.00 and 5.50 m3/sec at Besut Barrage, pre-saturation is recommended to be carried out over three phases. During normal irrigation supply period, flow rates of 5.00 m3/sec and 1.50 m3/sec for the Besut and Angga Barrages respectively, are to be maintained for the whole irrigation scheme. In irrigation block-wise, two WU-based performance indices, namely, adequacy (AI) and water productivity (WPI) were computed. The average water productivity was 0.31 kg/m3 and 0.25 kg/m3 during the main season and off-season, respectively. Two WU indices, WPI and AI, ranked the performance of the blocks and identified those having problems in water allocation and utilization. These indices revealed that the blocks using more water performed poorly in terms of water productivity. These indices could be used to rectify uneven distribution of water in the scheme.